Divergent roles of the Hippo pathway in the pathogenesis of idiopathic pulmonary fibrosis: tissue homeostasis and fibrosis - Ryusuke Kizawa; Jun Araya; Yu Fujita (Inflammation and Regeneration, 2023)
Abstract Idiopathic pulmonary fibrosis (IPF) is a progressive aging-related lung disease with a poor prognosis. Despite extensive research, the cause of IPF remains largely unknown and treatment strategies are limited. Proposed mechanisms of the pathogenesis of IPF are a combination of excessive accumulation of the extracellular matrix and dysfunctional lung tissue regeneration. Epithelial cell dysfunction, in addition to fibroblast activation, is considered a key process in the progression of IPF. Epithelial cells normally maintain homeostasis of the lung tissue through regulated proliferation, differentiation, cell death, and cellular senescence. However, various stresses can cause repetitive damage to lung epithelial cells, leading to dysfunctional regeneration and acquisition of profibrotic functions. The Hippo pathway is a central signaling pathway that maintains tissue homeostasis and plays an essential role in fundamental biological processes. Dysregulation of the Hippo pathway has been implicated in various diseases, including IPF. However, the role of the Hippo pathway in the pathogenesis of IPF remains unclear, particularly given the pathway’s opposing effects on the 2 key pathogenic mechanisms of IPF: epithelial cell dysfunction and fibroblast activation. A deeper understanding of the relationship between the Hippo pathway and the pathogenesis of IPF will pave the way for novel Hippo-targeted therapies.